Graphene oxide as a chemosensitizer: Diverted autophagic flux, enhanced nuclear import, elevated necrosis and improved antitumor effects. (February 2015) - Chen, Guan-Yu; Meng, Chia-Le; Lin, Kuan-Chen; Tuan, Hsing-Yu; Yang, Hong-Jie; Chen, Chiu-Ling; Li, Kuei-Chang; Chiang, Chi-Shiun; Hu, Yu-Chen
Abstract: Graphene oxide (GO) is a nanomaterial that provokes autophagy in CT26 colon cancer cells and confers antitumor effects. Here we demonstrated that both GO and the chemotherapy drug cisplatin (CDDP) induced autophagy but elicited low degrees of CT26 cell death. Strikingly, GO combined with CDDP (GO/CDDP) potentiated the CT26 cell killing via necrosis. GO/CDDP not only elicited autophagy, but induced the nuclear import of CDDP and the autophagy marker LC3. The nuclear LC3 did not co-localize with p62 or Lamp-2, neither did blocking autolysosome formation significantly hinder the nuclear import of LC3/CDDP and necrosis, indicating that autophagosome and autolysosome formation was dispensable. Conversely, suppressing phagophore formation and importin-α/β significantly alleviated the nuclear import of LC3/CDDP and necrosis. These data suggested that GO/CDDP diverted the LC3 flux in the early phase of autophagy, resulting in LC3 trafficking towards the nucleus in an importin-α/β-dependent manner, which concurred with the CDDP nuclear import and necrosis. Intratumoral injection of GO/CDDP into mice bearing CT26 colon tumors potentiated immune cell infiltration and promoted cell death, autophagy and HMGB1 release, thereby synergistically augmenting the antitumor effects. Altogether, we unveiled a mechanism concerning how nanomaterials chemosensitize cancer cells and demonstrated the potentials of GO as a chemosensitizer.